Ovicidal and Larvicidal Effects of Piper marginatum Essential Oil on Lutzomyia longipalpis (Lutz & Neiva, 1912) - Lucas Alexandre Farias de Souza; Michele Trombin de Souza; Mireli Trombin de Souza; Damaso Rubio-Vargas; João Carlos Minozzo; Beatriz Helena Lameiro de Noronha Sales Maia; Magda Clara Vieira da Costa-Ribeiro (Neotropical Entomology, 2026)
Lutzomyia longipalpis (Lutz & Neiva, 1912) is the main vector of the protozoan Leishmania infantum , the etiologic agent of Visceral Leishmaniasis (VL) in the American continent. In Brazil, the control of this sand fly species is difficult due to its resistance to chemical insecticides. The present study had the objectives of determining the chemical composition of Piper marginatum essential oil (EO) and to evaluating its ovicidal and larvicidal activity against Lu. longipalpis under laboratory conditions. To achieve this, a gas chromatography-mass spectrometry (GC-MS) was performed, and nine concentrations of the EO were tested on eggs and larvae: 0.25%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4%. Probit analysis estimated LC₅₀ and LC₉₀ values of 1.18% and 2.41% for eggs, and 0.91% and 1.71% for larvae, respectively. The major constituent of P. marginatum EO was 3',4'-methylenedioxypropiophenone, a phenylpropanoid commonly found in Piper species. All concentrations higher than 1% killed more than 50% of the treated larvae and rendered more than 50% of the eggs unviable. This is the first report of the toxicity of EO from a Piper plant against a sand fly species. This EO may constitute a viable alternative for controlling the immature stages of the primary vector of VL.